The Effectiveness of Storytelling Methods Using Image Media on The Expressive Language Abilities of Group A Children in Kindergarten Nasyiatul Ulum Bajur Waru Pamekasan - Mutmainnah; Sitti Farida (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
Children's expressive language abilities can be said to be still low because some children are not able to communicate fluently, the problem is that there are some children who are still less interested in the learning process, they prefer to play and have difficulty understanding the lessons taught by their teachers, get bored easily, and there are also children who are still afraid to interact. so teachers experience difficulties in the teaching and learning process. In Nayiatul Ulum Kindergarten, the learning process only involves question and answer activities and LKA (children's worksheet).  learning is only centered on the teacher. So the method of telling stories through picture media is one way to improve children's expressive language abilities. This research aims to analyze the effectiveness of the storytelling method using picture media on children's expressive language abilities at Nasyiatul Ulum Bajur Waru Pamekasan Kindergarten. The method used in this research is descriptive qualitative method. Collecting data used in this research was observation, interviews, documentation. Data analysis was carried out by data reduction, data presentation, conclusions. The results of this research show that the effectiveness of the storytelling method using picture media on children's expressive language abilities at Nasyiatul Ulum Kindergarten is good for children's expressive language. This can be seen from how the teacher applies the storytelling method using picture media on children's expressive ability to walk smoothly. , and children are also able to retell what the teacher has said.